Radiation-induced malignant fibrous histiocytoma of the occipital: a case report - Zhang, Guo-Bin (BioMed Central, 2014)
Malignant fibrous histiocytoma (MFH) is a rare neoplasm exhibiting a propensity for aggressive clinical behavior. Effective treatment modality is surgical resection with wide margins, but its rate of recurrence and metastasis is still high. Early detection and complete excision of the tumor is necessary. A MFH of the occipital developed in a 51-year-old woman eight years after surgery and radiation for medulloblastoma of the cerebellar vermis. The secondary neoplasm arose at the site of tumor resection within the irradiated field, and was resected. The development of sarcomas is a recognized complication of radiation therapy. The final diagnosis after the operation was MFH. Radiation-induced sarcoma (RIS) is well known, but radiation-induced MFH is relatively rare in the head and neck region, especially in the occipital. The imaging findings are not diagnosis specific, but strict follow-up within the radiation field by computerized tomography (CT) and magnetic resonance imaging (MRI) and appreciation of the expected latency period may help in providing the diagnosis of RIS.